Interleukin-18 Reduces Blood Glucose and Modulates Plasma Corticosterone in a Septic Mouse Model. Issue 4 (April 2017) - Yamashita, Hayato; Ishikawa, Michiko; Inoue, Taketo; Usami, Makoto; Usami, Yu; Kotani, Joji
ABSTRACT: Background: Dysregulation of glucose metabolism, including hyperglycemia with insulin resistance, is commonly observed in critically ill patients. Interleukin-18 (IL-18) improves the insulin resistance associated with obesity, but the relationship between IL-18 and glucose metabolism in sepsis was unclear. The purpose of this study was to investigate the influence of IL-18 on hyperglycemia during sepsis. Methods: Sepsis was induced using cecal ligation and puncture (CLP) in wild-type (WT) mice, IL-18 knockout (KO) mice, and IL-18 KO mice pretreated with recombinant IL-18. Blood glucose and plasma insulin, glucagon, and corticosterone were measured. The mRNAs for gluconeogenic enzymes ( g6pc, pck1 ) and activation of insulin signaling were also analyzed. Results: In both WT and IL-18 KO mice, CLP operation led to hyperglycemia that lasted longer (18 h) than after sham operation (6 h). Blood glucose levels in IL-18 KO mice were significantly higher than in WT mice, without alteration of insulin or glucagon levels. In IL-18 KO mice, insulin signaling in the liver and skeletal muscle was decreased during hyperglycemia as compared with WT mice without suppression of hepatic glucose production enzymes. Pretreatment with recombinant IL-18 reduced blood glucose levels after CLP. Additionally, corticosterone levels were higher after CLP in the presence of either endogenous or exogenous IL-18. Conclusion: IL-18 may reduce blood glucose by modulating insulin signaling in the liver during sepsis-induced hyperglycemia. IL-18 is an important factor associated with alterations in blood glucose during sepsis. Abstract : Supplemental Digital Content is available in the text